Neck and supraclavicular lymphadenopathy secondary to 9-valent human papillomavirus vaccination - Pereira, MP (2019)
We present two clinical cases of lymphadenopathy after vaccination with the human papillomavirus (HPV) 9-valent vaccine: an asymptomatic 11-year-old boy with inferior cervical and supraclavicular lymphadenopathy, and a 13-year-old girl who presented with lymphadenopathy. In both cases, medical history was unremarkable and there was no recent infection, or other clinical findings. Both adolescents had received the HPV 9-valent vaccine in the previous week. In the first case, blood tests, ultrasonography and biopsy were performed, while in the second, a watchful waiting strategy was adopted. In both cases, the lymphadenopathy resolved spontaneously. The boy received the second dose of the vaccine 6 months later and lymphadenopathy reappeared. The Naranjo scale was applied, classifying the events as definite (in the case of the boy) and probable (girl) adverse drug reactions. The vaccine is safe, but recognising this minor adverse event is important to prevent unnecessary investigation and reduce patient and parental anxiety.